Interdisciplinarity: A Catalyst for Faculty Engagement win Internationalization - Lisa Kim Childress (Journal of Global Initiatives, 2010)
Despite the benefits of international scholarship to higher education institutions, faculty engagement in internationalization remains a major challenge for many universities. This study sheds light on this problem by investigating the strategies used by two institutions to engage faculty in internationalization through interdisciplinarity. This study found that as interdisciplinarity emphasizes comparative approaches, it prompted faculty to advance the comprehensiveness of their scholarship through the integration of cross-cultural perspectives. Notably, this study presents a model to assist institutions in overcoming endogenous obstacles by providing three infrastructural components--time, place, and financial resources--for faculty to engage in interdisciplinary and international scholarship.